Morphological Studies on the Mouth Cavity of Bakerwali Goat (Capra hircus) of Jammu Region - Sharma, Kamal; Suri, Shalini; Devi, J; Doley, P J (Indian Journal of Veterinary Anatomy, 2012)
The present study was conducted on the mouth cavity of six adult Bakerwali goats. The vestibule of the mouth cavity was roomy with thorny papillae populated in the cavum oris. The thorny papillae larger in the vestibule of the upper cheek were absent on the labial part of the vestibule on the upper and lower cheeks. The papilla incisiva was half moon shaped. The hard palate had an average of 10 and 11 numbers of ridges on right and left sides, respectively being separated by a distinct median raphe. The caruncula sublingualis was roughly quadrilateral in shape. The vallate papillae were arranged in two indistinct rows with their number 16 on left and 17 on the right side. Lenticular papillae were thickly populated on the torus linguae. Various biometrical features of the hard palate and the tongue were recorded.